Comparison of Giving Beet and Date on Haemoglobin Among Pregnant Women with Anemia - Hamidah, Siti; Sulastri, Sulastri (STIKep PPNI Jawa Barat, 2024)
Aims : The purpose of this study is to evaluate the efficacy of administering beets and dates to pregnant women who have moderate anemia in terms of boosting their hemoglobin levels. Method : This research design employs a quasi-experimental study approach, which includes a pre-test and a post-test, as well as research instruments that make use of observation width and hydrogen bond level measuring equipment. It is the paired t-test that is utilized as the statistical test. Results : In the beetroot group, the results obtained were a mean pre test of 10.09 and a mean post test of 12.2 so it can be concluded that the mean difference is 1.3 (10.09- 12.2) and P value = 0.329 (P > α) so It can be concluded that the comparison of increasing hemoglobin levels in the beetroot group is more effective than the dates group for pregnant women in the third trimester at BPM Siti Hamidah Conclusion : Giving beetroot juice is more beneficial in boosting the HB levels of pregnant women with mild anemia, according to BPM Siti Hamidah.